2023
DOI: 10.1097/jcma.0000000000000899
|View full text |Cite
|
Sign up to set email alerts
|

Current developments and therapeutic potentials of Exosomes from Induced pluripotent stem cells (iPSCs)-derived mesenchymal stem cells (iMSCs)

Abstract: Mesenchymal stem cells (MSCs) are multipotent cells derived from adult human tissues that have the ability to proliferate in vitro and maintain their multipotency, making them attractive cell sources for regenerative medicine. However, MSCs reportedly show limited proliferative capacity with inconsistent therapeutic outcomes due to their heterogeneous nature. On the other hand, induced pluripotent stem cells (iPSC) have emerged as an alternative source for the production of various specialized cell types via t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 101 publications
0
3
0
Order By: Relevance
“…[193][194][195] Exosomes are products of the paracrine mechanism of stem cells, are more rapidly utilized than stem cells themselves, and have a wide range of clinical applications. [196][197][198] Regev-Rudzki N et al 194 examined the therapeutic effects of MSC-Exos during fracture healing in a CD9−/− mouse model and found that MSC-Exos were effective in promoting fracture healing. Zhang et al 199 reported results of implanting human embryonic-derived exosomes in a rat model of cartilage defect and found that exosome treatment resulted in the complete recovery of cartilage and subchondral bone by the 12th week.…”
Section: Stem Cell Exosomes Promote Bone Regenerationmentioning
confidence: 99%
See 2 more Smart Citations
“…[193][194][195] Exosomes are products of the paracrine mechanism of stem cells, are more rapidly utilized than stem cells themselves, and have a wide range of clinical applications. [196][197][198] Regev-Rudzki N et al 194 examined the therapeutic effects of MSC-Exos during fracture healing in a CD9−/− mouse model and found that MSC-Exos were effective in promoting fracture healing. Zhang et al 199 reported results of implanting human embryonic-derived exosomes in a rat model of cartilage defect and found that exosome treatment resulted in the complete recovery of cartilage and subchondral bone by the 12th week.…”
Section: Stem Cell Exosomes Promote Bone Regenerationmentioning
confidence: 99%
“…Exosomes are tiny vesicles secreted by living cells 191,192 that carry relevant proteins, lipids, nucleic acids, and other substances derived from late endonucleosomal multivesicular bodies, which play an important role in intercellular information transfer 193–195 . Exosomes are products of the paracrine mechanism of stem cells, are more rapidly utilized than stem cells themselves, and have a wide range of clinical applications 196–198 . Regev‐Rudzki N et al 194 .…”
Section: Stem Cell Exosomes In Regenerative Medicinementioning
confidence: 99%
See 1 more Smart Citation